Thickest to thinnest....
0.33m , 0.3mm, 0.275mm, 0.25mm
Answer:
A, B, F
Step-by-step explanation:
2/3 - x + 1/6 = 6x
Collect like terms
2/3 + 1/6 = 6x + x
(4+1) / 6 = 7x
5/6 = 7x
x = 5/6 ÷ 7
= 5/6 × 1/7
x = 5/42
a) 4 - 6x + 1 = 36x
4 + 1 = 36x + 6x
5 = 42x
x = 5/42
Equivalent to the last step of the simplification above
b) 5/6 - x = 6x
5/6 = 6x + x
5/6 = 7x
This is equivalent to the third step of the simplification
c) 4 - x + 1 = 6x
4 + 1 = 6x + x
5 = 7x
x = 5/7
Not equivalent to any of the steps in the simplification above
d) 5/6 + x = 6x
5/6 = 6x - x
5/6 = 5x
x = 5/6 ÷ 5
= 5/6 × 1/5
x = 5/30
Not equivalent to any of the steps in the simplification above
e) 5 = 30x
x = 5/30
Not equivalent to any of the steps in the simplification above
f) 5 = 42x
x = 5/42
Equivalent to the last step of the simplification above
Simplify the following:n^6/n^2
Combine powers. n^6/n^2 = n^(6 - 2):n^(6 - 2)
6 - 2 = 4:Answer: n^4 thus b: is you Answer
Answer:
let 'a' be the first term, 'd' be the common difference between all the terms of the sequence
Step-by-step explanation:
therefore, a = 3,
and, d = -9 -3
= -12
hence the 14th term would be,
=> a + 13d
=> 3 + 13( -12 )
=> 3 - 156
=> - 153